2019
DOI: 10.1002/rth2.12226
|View full text |Cite
|
Sign up to set email alerts
|

Hemostatic complications associated with ventricular assist devices

Abstract: Hemostatic complications are common in patients with ventricular assist devices. The pathophysiologic mechanisms that lead to dysregulated hemostasis involve complex interactions between device surface, sheer stress, and blood flow. These factors lead to various manifestations that require a thorough understanding of the interplay among platelets, coagulation factors, and red cells. In this article, we review the pathophysiology of hematologic complications (bleeding, acquired von Willebrand disease, heparin‐i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 103 publications
0
23
0
Order By: Relevance
“…Two examples of such experience are a small study of seven patients using dabigatran with no excess rate of bleeding or thrombosis ( 65 ) and a single center, randomized trial of dabigatran vs. warfarin which was terminated early due to increased thromboembolic events associated with dabigatran ( 66 ). Additionally, given the negative experience with dabigatran use in mechanical heart valves, routine use could not be recommended without more reassuring clinical trials ( 67 ).…”
Section: Doacmentioning
confidence: 99%
“…Two examples of such experience are a small study of seven patients using dabigatran with no excess rate of bleeding or thrombosis ( 65 ) and a single center, randomized trial of dabigatran vs. warfarin which was terminated early due to increased thromboembolic events associated with dabigatran ( 66 ). Additionally, given the negative experience with dabigatran use in mechanical heart valves, routine use could not be recommended without more reassuring clinical trials ( 67 ).…”
Section: Doacmentioning
confidence: 99%
“…The prevalence of heart failure in the United Sates is increasing; it is estimated that more than 870 000 new cases will be diagnosed each year 44 . Heart transplantation remains the best therapy for end‐stage heart failure; however, few patients are deemed adequate candidates for transplant, which has led to the development of mechanical therapies to augment cardiac function.…”
Section: Continuous Extracorporeal Circulatory Devicesmentioning
confidence: 99%
“…Despite evolving practices in anticoagulation and antithrombotic therapy, thromboembolic events are still common in patients with LVADs 44 . Data from the REMATCH study showed the following relative incidence rates for adverse events in LVADS compared to medical therapy: non‐neurologic bleeding (9.47), peripheral embolic events (3.92), myocardial infarction (0.65), and neurologic dysfunction (eg, stroke, TIA, toxic/metabolic encephalopathy) (4.35).…”
Section: Continuous Extracorporeal Circulatory Devicesmentioning
confidence: 99%
“…7 In cardiovascular conditions with elevated shear stress, there is constant conformational change and unfolding of the ultra-large vWF multimers exposing the cleavage site to the metalloprotease enzyme ADAMTS-13 resulting in loss of the high-molecularweight multimers. 8 Pediatric AvWS is most frequently associated with congenital or acquired heart defects including valve stenosis, ventricular septal defects, hypertrophic cardiomyopathies, pulmonary hypertension, VADs, and extracorporeal membrane oxygenation. 7 The clinical presentation of AvWS ranges from asymptomatic to bleeding, thrombosis, or a predisposition to both.…”
Section: Pathogenesis Presentation and Diagnosis Of Avwsmentioning
confidence: 99%
“…It can develop within a few hours of VAD support, last as long as the VAD is in place, and resolves within a few hours of VAD termination. 8 Highmolecular-weight multimers are more rapidly destroyed with continuous flow axial devices compared with centrifugal devices. 2 The high shear stress of axial devices resulted in decreased levels in 83% of patients within 24 hours of implantation.…”
Section: Acquired Von Willebrand Syndrome and Vad-supported Patientsmentioning
confidence: 99%